Girls exhibit greater empathy than boys following a minor accident - Benenson, Joyce F. (Sci Rep, 2021)
Hundreds of studies find that girls and women report feeling greater empathy than boys and men in response to adverse events befalling others. Despite this, few non-self-report measures demonstrate similar sex differences. This produces the oft-cited conclusion that to conform to societal expectations of appropriate sex-typed behavior females report higher levels of empathy. Several studies of sex differences in areas of brain activation and on infants’ and young children’s behavior however provide suggestive findings that self-reports reflect actual underlying sex differences in experiencing concern about others. We demonstrate using behavioral indices that females experience more empathy than males after witnessing an adverse event befall a same-sex classmate. In our study, one member of a pair experienced a minor accident on the way to constructing a tower while a bystander observed. We measured whether bystanders ceased their ongoing activity, looked at the victim, waited for the victim to recover from the accident, and actively intervened to help the victim. Female more than male bystanders engaged in these activities. These behavioral results suggest that an adverse event produces different subjective experiences in females than males that motivate objectively different behaviors, consistent with findings from self-report measures of empathy.